ANALISIS TINGKAT PENGANGGURAN DAN KEMISKINAN TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Aswanto, Aswanto; Edward, Yurnal (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
Economic growth is one of the benchmarks that can be used to see the level of welfare of a country. Unemployment and poverty rates are macroeconomic problems that will be obstacles in increasing sustainable economic growth. The purpose of this study is to analyze and explain the level of unemployment and poverty on Indonesia's economic growth. The research method used is a descriptive research method with a qualitative approach, using the Eviews 13 data processing tool. The results of the analysis show that the level of unemployment and poverty have a negative and significant effect on Indonesia's economic growth, as evidenced by the determination coefficient value of 0.8496 or 84.96%, meaning that the influence of Unemployment and Poverty is 84.96% and the remaining 15.04% is influenced by other variables not examined in this study.